A critical analysis as to whether a company is entitled to carry forward assessed losses if such company has traded but has derived no income therefrom - Coetzee, Izak Jacobus (Department of Finance and Tax, 2021)
The Income Tax Act No 58 of 1962 provides for tax to be levied on an annual basis (i.e. income and expenditure are generally calculated and determined in respect of a single year of assessment). Section 20(1) makes provision for the possibility that the allowable deductions may exceed a taxpayer's income by allowing for the carrying forward of any balance of assessed loss to subsequent years of assessment. It therefore provides for taxpayers to utilise assessed losses determined in previous tax periods against the income derived in future tax periods. Our courts have decided that a company which does not trade during a specific year of assessment forfeits its right to carry forward its balance of assessed loss from the preceding year of assessment. What has been left undecided in our superior courts however (although has been considered in our Tax Courts), is whether a company would also forfeit its right to carry forward its balance of assessed loss in the event where such a company carried on a trade during the current year of assessment, but derived no income therefrom. The primary research question in this study is whether a company would be allowed to carry forward its balance of assessed loss determined at the end of its previous year of assessment to its current year of assessment, in circumstances where it derived no ‘income' from its trading activities during the current year of assessment. This study also considers, as a secondary research question, whether the recent proposals made by Treasury in terms of the Budget Speech held on 26 February 2020, would have an impact on the primary research question. In order to address the primary and secondary research questions, this study considers the wording of section 20 in the light of the guidance on interpreting fiscal statutes as provided by our courts. The study also considers the views expressed in our courts in relation to section 20(1) as well as the relevant commentary on these views. Furthermore, the study considers SARS' view on section 20 as well as whether the recent proposals made by Treasury have an impact on the carrying forward of a company's balance of assessed loss. It is concluded that in terms of the recent proposal made by Treasury, a company whose trading activities result in a loss should be unaffected by the proposed amendments, although this can only be confirmed once the proposed legislation in this regard has been made available. It is further concluded that a superior court has not yet interpreted section 20(1) in terms of the current approach to the interpretation of statutes, and it is submitted that a superior court may come to the conclusion that a company would be allowed to carry forward its balance of assessed loss determined at the end of its previous year of assessment to its current year of assessment, even though it had derived no income from its trading activities during its current year of assessment.